Aktivitas Antidiabetes Ekstrak Air-Etanol, n-Heksan, dan Etil Asetat Uwi Banggai (Dioscorea alata L.) Dengan Metode Induksi Aloksan Pada Mencit Jantan (Mus musculus): Antidiabetic Activity of Water-Ethanol, N-Hexane, and Ethyl Acetate Extracts of Dioscorea Alata L. Using Alloxan Induction Method on White Rats (Mus musculus) - Khaerati, Khildah; Amini, Delina; Ihwan (Universitas Tadulako, 2020)
Hyperglycemia is a condition of increased blood glucose levels caused by insufficient insulin enzymes produced to control blood sugar levels in the body. This study aimed to determine the activity of ethanol-water, nhexane, and ethyl acetate extracts of Dioscorea alata L. in reducing blood glucose levels in hyperglycemia modeled mice that were given intraperitoneal alloxan induction. 25 white rats were divided into 5 groups of test animals. Each group consists of 5 mice. The first group was given 0.5% sodium carboxymethylcellulose solution as a placebo, the second group was given 0.65 mg/kg BW glibenclamide as a positive comparison group, the third group was given the suspension of ethanol-water extract, the fourth group was given n-hexane extract, and the fifth group was given ethyl acetate extract at a dose of 140 mg/kg BW. The test preparation was orally given within 14 days of testing. The test was measured as the initial blood glucose levels of mice after alloxan induction and after giving the test preparation suspension. The results of the qualitative analysis illustrate that the water-ethanol extract can reduce blood glucose levels by 31.39%, n-hexane extract by 51.11%, and ethyl acetate extract by 50.77%. The results of quantitative analysis using One Way ANOVA method showed that the water-ethanol, n-hexane, and ethyl acetate extracts significantly decreased the blood glucose levels of mice. The best antidiabetic activity was ethyl acetate extract with a decrease in rat blood glucose levels by 169 mg/kg BW.